Ephrin and Eph receptor signaling in female reproductive physiology and pathology - Adu-Gyamfi, Enoch Appiah; Czika, Armin; Liu, Tai-Hang; Gorleku, Philip Narteh; Fondjo, Linda Ahenkorah; Djankpa, Francis Tanam; Ding, Yu-Bin; Wang, Ying-Xiong (Biology of reproduction, 2021)
Ephrins are ligands of Eph receptors (Ephs); both of which are sorted into two classes, A and B. There are five types of ephrin-As (ephrin-A1–5) and three types of ephrin-Bs (ephrin-B1–3). Also, there are 10 types of EphAs (EphA1–10) and six types of EphBs (EphB1–6). Binding of ephrins to the Eph receptors activates signaling cascades that regulate several biological processes such as cellular proliferation, differentiation, migration, angiogenesis, and vascular remodeling. Clarification of their roles in the female reproductive system is crucial to understanding the physiology and pathology of this system. Such knowledge will also create awareness regarding the importance of these molecules in diagnostic, prognostic, and therapeutic medicine. Hence, we have discussed the involvement of these molecules in the physiological and pathological events that occur within the female reproductive system. The evidence so far suggests that the ephrins and the Eph receptors modulate folliculogenesis, ovulation, embryo transport, implantation, and placentation. Abnormal expression of some of these molecules is associated with polycystic ovarian syndrome, ovarian cancer, tubal pregnancy, endometrial cancer, uterine leiomyoma (fibroids), cervical cancer, and preeclampsia, suggesting the need to utilize these molecules in the clinical setting. To enhance a quick development of this gradually emerging field in female reproductive medicine, we have highlighted some “gaps in knowledge” that need prospective investigation. Summary sentence The ephrin and Eph receptors are expressed throughout the female reproductive system, regulate the functioning of this system and associate with a number of obstetric and gynecologic disorders. Graphical Abstract